Cross‐fertilizing aquatic and terrestrial research to understand predator risk effects. (4th August 2014) - Wirsing, Aaron J.; Heithaus, Michael R.; Frid, Alejandro
<x xml:space="preserve">Abstract</x> Research that conceptually transcends boundaries between aquatic and terrestrial ecosystems has a long history of increasing insight into ecology and evolution. To stimulate further cross‐fertilization between studies that focus on different ecosystems, we highlight several insights on risk effects—the costs of antipredator behavior—that have emerged in part because of combined advances in aquatic and terrestrial systems. Namely, risk effects (1) are not restricted to structured landscapes where antipredator behavior is easily measurable, (2) can be substantial even when prey experience very low predation rates, (3) are contingent on a three‐way interaction between the hunting mode of the predator, escape tactic of the prey, and features of the landscape/physical environment, and (4) can interact with direct predation (consumption) and resource availability (through its effects on prey energy state) to control consumer population size. We conclude by highlighting the value of exploring differences between aquatic and terrestrial risk effects and offering a prospectus for future studies of antipredator behavior and its ecological importance in both eco‐domains. WIREs Water 2014, 1:439–448. doi: 10.1002/wat2.1039 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.